Does Sharing Economy Have a Moral Capital? Comparing Semantic Networks in Social Media and News Media - Ravindran, Kiron; Colleoni, Elanor; Elanor, Colleoni; Nuccio, Ludovico; Illia, Laura (Canadian Center of Science and Education, 2021)
Sharing Economy organizations appear to enjoy positive moral capital associated with supporting local entrepreneurs, the economy, and the environment. However, they operate in a regulatory limbo allowing them to engage in business practices that would not be permitted in other sectors. Hence a question remains: Does Sharing Economy (SE) have a moral capital? To explore whether the sharing economy has a moral capital, we explored the discussions around Uber after a number of scandals in 2017 in news media and on Twitter. Our findings show that news media play a critical role in developing and maintaining a positive moral capital of Uber, while the general public on Twitter tend to be more negative and do not afford SE much moral capital.
Keywords: Sharing economy; Moral capital; Sharing economy controversies; Media coverage; Twitter; 63 Sociología::6307 Cambio y desarrollo social; ODS 8 - Trabajo decente y crecimiento económico